2015
DOI: 10.1309/ajcpxgraimb4ctq3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Targeted Therapy in Advanced Non–Small Cell Lung Cancer: Suitability of Endobronchial Ultrasound Transbronchial Needle Aspiration

Abstract: Our study demonstrates that EBUS-TBNA can be effectively used not just for diagnosis but also for complete mutational testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 30 publications
4
47
1
1
Order By: Relevance
“…Conversely, ALK (6.4%) rearrangements were more frequently identified in young female and never-smoker patients, confirming that different clinical characteristics are often associated with different molecular alterations 39. Comparing the present results to those obtained in our previous NSCLC series,30 we found concordant frequencies of KRAS alterations but significantly higher rates of ALK translocated tumours (present series 6.4% vs historical series 3.5%; p-value <0.005). This might be due to both the implementation of immunohistochemistry as an adjunct tool in ambiguous ALK FISH test results40 and the recent approval (January 2017) of crizotinib as first-line therapy for ALK-translocated NSCLC by the Agenzia Italiana del Farmaco (AIFA) that increased the number of ALK test orders.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Conversely, ALK (6.4%) rearrangements were more frequently identified in young female and never-smoker patients, confirming that different clinical characteristics are often associated with different molecular alterations 39. Comparing the present results to those obtained in our previous NSCLC series,30 we found concordant frequencies of KRAS alterations but significantly higher rates of ALK translocated tumours (present series 6.4% vs historical series 3.5%; p-value <0.005). This might be due to both the implementation of immunohistochemistry as an adjunct tool in ambiguous ALK FISH test results40 and the recent approval (January 2017) of crizotinib as first-line therapy for ALK-translocated NSCLC by the Agenzia Italiana del Farmaco (AIFA) that increased the number of ALK test orders.…”
Section: Discussionsupporting
confidence: 84%
“…Level I alterations in EGFR and/or KRAS were present in 286 non-squamous NSCLC, including 2 cases with concurrent EGFR and KRAS mutations. In the present series, we found a significantly higher percentage of EGFR -mutated patients than our previously published historical series analysed with Sanger sequencing or real-time-based assays30 (present series 22.4% vs historical series 15.1%; p value <0.005). This could be related to the higher sensitivity of the current NGS analysis; however, we adopted a threshold of variant calls of 5% that is comparable with the sensitivity of the real-time assay used in the previous study 31.…”
Section: Discussioncontrasting
confidence: 60%
“…The clinical importance of molecular testing is well established. The debate regarding the adequacy of cytological versus histologic samples for molecular testing is ongoing [16] , but to date, studies have demonstrated excellent results for the detection of EGFR and ALK mutations with EBUS-TBNA [21,22] . The result of our data echoes the findings in previous studies with 100% of the samples from adenocarcinoma satisfactory for EGFR and ALK testing.…”
Section: Discussionmentioning
confidence: 99%
“…The success in performing molecular tests on TBNA samples depends on the absolute number and percentage of malignant cells present in the sampled material, on quality of cell preservation and on type and sensitivity of the test itself (17,39). Recent reports from high-volume centers indicate that 72-97% of EBUS-TBNA samples are appropriate for testing the most frequently used prognostic markers of lung cancer, namely EGFR, ALK and KRAS (17,25,39,40). Both smear and cell block preparation, or core tissue, can be utilized for molecular testing (17,23); however, while EGFR and KRAS status can be determined using all three specimen preparation techniques, the ALK translocation is best assessed using cell block and core tissue (17).…”
Section: Molecular Testingmentioning
confidence: 99%